Carotenoid Profile of Tomato Sauces: Effect of Cooking Time and Content of Extra Virgin Olive Oil - Vallverdu-Queralt, Anna; Regueiro, Jorge; Rinaldi de Alvarenga, Jose Fernando [UNESP]; Torrado, Xavier; Lamuela-Raventos, Rosa M. (Mdpi Ag, 2015)
The consumption of carotenoid-rich vegetables such as tomatoes and tomato sauces is associated with reduced risk of several chronic diseases. The predominant carotenoids in tomato products are in the (all-E) configuration, but (Z) isomers can be formed during thermal processing. The effect of cooking time (15, 30, 45 and 60 min) and the addition of extra virgin olive oil (5% and 10%) on the carotenoid extractability of tomato sauces was monitored using liquid chromatography-tandem mass spectrometry (LC-ESI-MS/MS) and LC-ultraviolet detection (LC-UV). The thermal treatment and the addition of extra virgin olive oil increased the levels of antioxidant activity, total carotenoids, Z-lycopene isomers, -carotene and -carotene. These results are of particular nutritional benefit since higher lycopene intake has been associated with a reduced risk of lethal prostate and a reduction of prostate-specific antigen (PSA) levels. Moreover, -carotene has been reported to suppress the up-regulation of heme oxygenase-1 gene expression in a dose dependent manner and to suppress UVA-induced HO-1 gene expression in cultured FEK4.
Keywords: LC-ESI-MS; MS; LC-UV; C30 column; -carotene; lycopene; antioxidant capacity